2020
DOI: 10.1097/md.0000000000020986
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral carbon dioxide embolism after kidney cancer laparoscopic surgery with full neurological recovery

Abstract: Rationale: Cerebral carbon dioxide embolism (CCDE) is a rare cause of stroke and is a recognized life-threatening complication.CCDE may result from direct intravascular CO 2 insufflation during surgery. Due to the lack of typical clinical manifestations, the disease is often missed or mistaken for another condition. The clinical signs and symptoms depend on the speed and volume of embolized gas entering the blood and the patient's condition. In particular, patent foramen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Li et al . reported cerebral infarction case due to CO 2 embolism after laparoscopic partial nephrectomy, which was associated with postoperative hemiparesis, vomiting, and deep sedation 6 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Li et al . reported cerebral infarction case due to CO 2 embolism after laparoscopic partial nephrectomy, which was associated with postoperative hemiparesis, vomiting, and deep sedation 6 …”
Section: Discussionmentioning
confidence: 97%
“…Li et al reported cerebral infarction case due to CO 2 embolism after laparoscopic partial nephrectomy, which was associated with postoperative hemiparesis, vomiting, and deep sedation. 6 Effective imaging examinations in gas embolism include TEE and CT, which can confirm gas in vessels. 4,7 It is difficult to obtain CT scan intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…While gas emboli are already a rare complication, those traveling to the cerebral vasculature, as observed in our patient, are even rarer and can precipitate a stroke or transient ischemic attack (TIA). The reported incidence rate of gas embolism following laparoscopic procedures is as low as 0.15%, with an estimated mortality rate as high as 30% [ 6 ]. Kulkarni et al.…”
Section: Discussionmentioning
confidence: 99%
“…CO2 embolism may be asymptomatic but can lead to neurologic injury, cardiovascular collapse, and even death. The presentation of CO2 embolism depends on the speed and volume of the embolized gas that enters the blood [7].…”
Section: Discussionmentioning
confidence: 99%